Temporal Resolution Abilities in Musicians and No Musicians Violinists - Monteiro, Ricardo Alexandre Martinez; Nascimento, Franklin Martins; Soares, Carla Debus; Ferreira, Maria Inês Dornelles da Costa (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The temporal resolution is the perception of a time interval in which the individual discriminates two sounds being a skill involved in music.Objective: To identify the performance of temporal resolution in musicians and no musicians violinists and correlate it with the average of the thresholds of low frequencies and acute as well as the time of exposure to music daily.Method: This study was characterized by be prospective and compared between two groups, one consisting of 20 violinists and other musicians for 20 semi no musicians matched for age and education were submitted to audiological evaluation and to the test Gaps In Noise (GIN) to evaluate the temporal resolution.Results: The test performance of the GIN group of musicians was not significant in the control group is in the right ear (RE) or left (LE). The correlation between the average high frequencies for the LE with the GIN test was (p = 0.001) in the control group. The average frequencies for both ears in the group of musicians was statistically significant and the highest values for RE (p = 0.001).Conclusion: There was no difference between the performance of the GIN test for both groups as well as the correlation between duration of daily exposure to music and GIN. The audiometric threshold of high frequencies seemed to be relevant for testing GIN.
Keywords: music; auditory threshold; auditory perception